Herbicidas imidazolinonas: fitotoxicidade em arroz tolerante, azevém na entressafra e efeito do resíduo em soja - Oliveira, Maurício Limberger de (2017)
The Clearfield® system of rice was developed as a control alternative of weeds in this crop, mainly weedy rice. Currently there are several rice varieties tolerant to herbicides of imidazolinones chemical group. The responses of the varieties to these herbicides may be different as a function of the application of high doses and due to the low temperature stress that can occur in anticipated seeding dates. These conditions may result in phytotoxicity and in grain yield losses. Furthermore, imidazolinones are characterized by presenting high persistence in soil, which may hamper the implantation of crops in rotation with rice, such as soybean. The phytoremediation and area drainage in the fall-winter period may be strategies to reduce the persistence of these herbicides. Therefore, the study objectives of this dissertation were to evaluate the phytotoxicity of different rates of the formulated mixture of the herbicides imazapyr+imazapic, applied in pre and post-emergence, in two tolerant rice varieties (Article I), as well as to evaluate the phytoremediation capacity of the residue of imazapyr+imazapic in the soil by ryegrass, in two drainage conditions of the area in the off-season, and the effect on soybean growth (Article II). The experiments were carried out on the field between the years of 2015 and 2017, in the lowland experimental area of the Universidade Federal de Santa Maria, Brazil, in a randomized complete block. In the article I experiment, the studied factors were two tolerant rice varieties (Guri INTA CL and IRGA 424 RI) and the rates of the formulated mixture of the herbicides imazapyr+imazapic (525+175 g a.i. kg-1) of 0, 140, 210, 280, 350, and 420 g c.p. ha-1. In the article II, the factors were the rates residue of herbicides imazapyr+imazapic (0, 210, and 420 g c.p. ha-1), applied in 2015/16 crop season on the irrigated rice, and the presence or absence of ryegrass in the off-season. One of the experiments of the second article was carried out under deficient drainage condition in the off-season, and the other under efficient drainage. The maximum phytotoxicity found in rice varieties was 13%. The other variables studied were not influenced by herbicides rates. The application of the formulated mixture of the herbicides imazapyr+imazapic, in soils with low organic matter content and pH close to 6, causes low phytotoxicity to the tolerant rice varieties Guri INTA CL and IRGA 42 RI up to three times the recommended rate, not influencing their grain yield.. The residue in the soil of the application of 420 g c.p. ha-1 of the formulated mixture of the herbicides imazapyr+imazapic, performed 129 days before seeding, causes phytotoxicity and dry mass reduction of ryegrass in deficient drainage condition in the off-season in irrigated rice areas. Soybean, when seeded 359 days after application, has its initial root and shoot growth hampered by rates residue of 210 and 420 g c.p. ha-1 in the deficient drainage condition in the off-season, independent of ryegrass cultivation. However, grain yield is not affected.